HE WAYS OF INCREASING THE BIOAVAILABILITY OF LEGUMES IN THE TECHNOLOGY OF FAST-PREPARATION FOOD CONCENTRATES - S. A. Urubkov; A. A. Korolev; S. O. Smirnov (Современная наука и инновации, 2022)
Globally, the replacement of animal protein with more available plant proteins in food is relevant from the point of view of a more sustainable food supply.